2001
DOI: 10.1089/10445490152717596
|View full text |Cite
|
Sign up to set email alerts
|

Number of Aβ Inoculations in APP+PS1 Transgenic Mice Influences Antibody Titers, Microglial Activation, and Congophilic Plaque Levels

Abstract: There have been several reports on the use of beta-amyloid (Abeta ) vaccination in different mouse models of Alzheimer's disease (AD) and its effects on pathology and cognitive function. In this report, the histopathologic findings in the APP+PS1 doubly transgenic mouse were compared after three, five, or nine Abeta inoculations. The number of inoculations influenced the effects of vaccination on Congo red levels, microglia activation, and anti-Abeta antibody titers. After three inoculations, the antibody tite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
2
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 20 publications
6
56
2
1
Order By: Relevance
“…It has also been shown to attenuate memory loss in APP+PS1 transgenic mice (Morgan et al, 2000) and in singly transgenic APP mice (Janus et al, 2000). We have also shown that there appears to be a dependence on microglial activation for the removal of compact, Congophilic amyloid deposits following active vaccination (Wilcock et al, 2001) and following direct intracranial injection of anti-Aβ antibodies (Wilcock et al, 2003). In the current study we show that Aβ vaccination results in generation of significant anti-Aβ antibody titers, reduced amyloid deposition and increased microglial activation associated with the remaining compact amyloid deposits.…”
Section: Discussionmentioning
confidence: 66%
“…It has also been shown to attenuate memory loss in APP+PS1 transgenic mice (Morgan et al, 2000) and in singly transgenic APP mice (Janus et al, 2000). We have also shown that there appears to be a dependence on microglial activation for the removal of compact, Congophilic amyloid deposits following active vaccination (Wilcock et al, 2001) and following direct intracranial injection of anti-Aβ antibodies (Wilcock et al, 2003). In the current study we show that Aβ vaccination results in generation of significant anti-Aβ antibody titers, reduced amyloid deposition and increased microglial activation associated with the remaining compact amyloid deposits.…”
Section: Discussionmentioning
confidence: 66%
“…These include the prevention of neurotoxic fibril formation (27), efflux of soluble A␤ from the brain to the plasma, also known as the peripheral sink mechanism (32), and microglia-mediated removal of A␤ (1,7,34,35,41). Results from our study indicate that all three mechanisms may be at work.…”
Section: Discussionmentioning
confidence: 70%
“…CD45 is a tyrosine phosphatase that plays critical roles in immune receptor signaling. CD45 expression levels are elevated in reactive microglia in the AD brain (Masliah et al, 1991) and in murine models of the disease (Wilcock et al, 2001). We also found that there was an ibuprofen-mediated 49% reduction ( p Ͻ 0.05) in the expression of the complement receptor 3 subunit CD11b (Fig.…”
Section: Resultsmentioning
confidence: 99%